VIOLENCE LINKED TO ARMED CONFLICTS AND THEIR IMPACT ON THE LOGICAL REASONING OF THE INHABITANTS OF THE TERRITORY OF RUTSHURU IN NORTH KIVU, IN THE EAST OF THE DEMOCRATIC REPUBLIC OF CONGO (DRC). - BALUME BAKULIKIRA, Blaise; Kimbuani Mabella, Prof. Gaston; Valentin, Ass. Bahati (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
This article, which focuses on violence linked to armed conflicts and their impact on the logical reasoning of the inhabitants of the territory of Rutshuru, wanted to identify the type of reasoning dominant among the subjects of the Territory of Rutshuru; show the level of exposure of the subjects to violence and verify if the level of exposure impacts the reasoning of the inhabitants of Rutshuru Territory. The results obtained showed that more than 2/3 of the subjects lack logic in their reasoning. So, therefore, they are not able to give the answer that goes against their personal beliefs. Also, more than half of the subjects were highly exposed to armed-related violence in the Rutshuru Territory, but exposure to violence does not impact on reasoning (p=0.87).